Altı yaş grubu çocuklarında başkasının bakış açısını alma yetisi üzerinde eğitici drama programının ve aile tutumlarının etkisinin incelenmesi - Akın, Yeliz (My University, 2002)
The aim of this research is to find out whether the perspective taking ability (pre-empathy) can be gained by educational drama among six age preschool education children and whether parential attitude is affective on this ability or not. Sample of this research consisting pre-post test, experimental and control groups, covers 90 children and their parents. The socia-econmic levels in the sample are taken according to the SIS categories and experimantal units are randomly assigned to low-high-middle levels. Children from each level are grouped as 15 experimental and 15 control. 25 drama activities are applied to the children in experimental group and the interaction of the content of these activities with the perspective taking is evaluated by three experts. While 25 special drama activities like discussion and support type are applied to the experimental group repeatedly, only general education activities are applied to the control group. In the research, innner test reliability is measured by Chronbach Alpha applied to 90 children and the time reliability (consistency) is measured by test retest technique appolied to 30 chieldren twice in a month. Perspective Taking Ability Test prepared by Prof. Dr. Bekir Onur and research assistant Tülin Şener is used in order to measure the perspective taking ability consisting 3 sublevels. Its design reliability is evaluated by the experts. In order to measure the parent attitude PARI consisting 5 sublevels, each ones' reliability and adequacy evaluated, prepared by E. S. Schaefer and R. Q. Bell and translated in Turkish by Güney Le Comple, Ayhan Le Compte and Şenay Küçük is used. To get the information on the demographic conditions of the families, Individual İnformation Form prepared by the researcher is used. The data obtained from the experimantal and the control groups is analyzed by frequency, percentage, ANOVA and t-tests. The significance level is taken as 0.05 and 0.01. To test the time reliability of the measurement instrument, a test is applied to an independent sample twice in a month. It is seen that there is no difference between the results so that it is sensitive to time. Chronbach Alpha Item analyze is done to all items and subitems of the measurement instrument and seen that there is no need to delete any item from the test. As a result of the statistical analysis, it is found that educational drama activities have a positive effect on perspective taking ability. The t test results of the pre test scores indicating affective, cognitive, perseptive perspective taking sublevels shows homogenity at the beginning while they differ among experimental and control groups after the application. Socia-economic level variable, parent attitude variable, test status variable is analyzed with multiple variance analysis among affective, cognitive, perseptive perspective taking sublevels. Related results are tabulated in conclusion and discussion parts.
Keywords: Çocuk Eğitimi